Review on Curvelet Transform and Its Applications - Kourav, Arvind; Prashant Singh (Asian Journal of Electrical Sciences, 2013)
The Curve let Transform gives better performance in terms of PSNR. Face recognition is very important for many applications such as: video surveillance, criminal investigations and forensic applications, secure electronic banking, mobile phones, credit cards, secure access to buildings. The curvelet transform is a multi scale directional trans-form, which allows an almost optimal non adaptive sparse representation of objects with edges. Curvelet have also proven useful in diverse fields beyond the traditional image processing application